Identidades literárias da violência na cidade do Rio de Janeiro : reconfiguração de forças e pluralização de vozes - Matte, Gustavo Arthur (2016)
OpposingJoão César de Castro Rocha’s thinking on the so called “dialectic of marginality” to Antonio Candido’s “dialectic of malandragem”, this study maps the social spaces which started to gradually claim and occupy a lieu of speech in the context of Brazilian contemporary literature – often around the theme of urban violence.It starts from the assumption that the first space to be occupied was that of urban peripheries, when Cidade de Deus emerged as a literary panorama of the slum from inside, using its ownsocial class perspective. Since it was a new phenomenon in the field of Brazilian literature, and since it poses a direct challenge to the cultural centrality of a touristic and homogeneous Rio de Janeiro (related to the South Zone of the city), Cidade de Deus (1997) –subsidized by the great success of the eponymous movie (2002) –highlighted the urgencyof a reconfiguration of forces and a pluralization of voices in the Brazilian cultural and literary fields. Under the influence of Cidade de Deusnot only cases of other peripheral writers appeared (such as Ferréz in São Paulo), but also indirect consequences were felt, for example: the necessity of other social voices to configure or reconfigure their participation in the system.Based on this particular reasoning, I have thus made speculations about the spaces of speech that started to act strongly through various publications. These spaces are: center; periphery; police; prison. Taking into account at least one narrative representing each of the points2, my intentions with this study are to identify perspectives of social classes in each of them, in such a way that we can understand how is that they answer to the “marginality challenge” by means of literature.